(g*p)**- CLOSED SETS IN TOPOLOGICAL SPACES - Ravi, K.; Helen, M.Pauline Mary; Padma, Anitha (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we have introduced a new class of sets called (g*p)**-closed sets which is properly placed in between the class of closed sets and the class of (g*p)**-closed sets. As an application, we introduce three new spaces namely, gT**p,T**p and T**p-spaces. We have also introduced (g*p)**-continuous and (g*p)**-irresolute maps and their properties are investigated.